Hierarchically structured evaporator with integrated water supply and evaporation layers to retard salt accumulation. (April 2022) - Li, Haoran; Yan, Zhe; Qian, Yinhao; Wang, Shiming; Liu, Xiaoyi; Yan, Shengnan
Highlights: A hierarchical solar evaporator was prepared to balance the water supply and demand. An appropriate water supply rate was obtained based on porosity adjustment. The upper layer prevented excessive wetting of the surface receiving photons. It was well operated in NaCl solution with a concentration close to its saturation. Abstract: Solar steam generation offers a greener alternative to replace traditional freshwater production projects consuming fossil fuels. However, salt accumulation in the evaporation layer is a major stumbling block restricting the development of high-efficiency solar steam generators. In this work, we introduce a hierarchically structured evaporator (HSE) with integrated water supply and evaporation layers for reducing the salt accumulation together with accelerating the water evaporation. The specially designed apertures of the lower layer endowed the HSE with high porosity (75.4%) and relative water content (10.4 times), ensuring sufficient water supply for interfacial evaporation. In addition, the dense skeleton of the upper evaporation layer enabled to prevent excessive wetting of the top surface receiving photos. An appropriate water supply rate was obtained based on porosity adjustment of HSE, which produced an impressive evaporation rate of 1.64 kg m −2 h −1 under one sun illumination. Meanwhile, a long-term operation of HSE in 25% (w/w) NaCl solution showed an evaporation rate fluctuating around 1.57 kg m −2 h −1 within 2.5 h illumination, and maintaining to 1.37 kg m −2 h −1 after 6 h illumination. These superior properties make HSE highly desirable for sustainable and rapid clean water production.